Early experience with the Penumbra SMART coil in the endovascular treatment of intracranial aneurysms: Safety and efficacy. Issue 6 (December 2016) - Stapleton, Christopher J; Torok, Collin M; Patel, Aman B
Background: Penumbra SMART coils differ from traditional microcoils used for endovascular coil embolization of intracranial aneurysms (IAs) in that they (1) become progressively softer from their distal to proximal end, rather than being of uniform stiffness, (2) have a tight conformational structure, and (3) have a more robust stretch-resistance platform. These properties aid in preventing microcatheter prolapse and coil herniation during coil deployment and in filling small pockets of the aneurysm sac. Objective/Methods: To determine the safety and efficacy of this device, the records of 17 consecutive patients with IAs treated with SMART coils were retrospectively analyzed. Results: Thirteen female and four male patients were identified. Eleven patients presented with subarachnoid hemorrhage, four had recurrent aneurysms, and two had incidentally discovered aneurysms. Twelve aneurysms (two of which were recurrent) were treated with stand-alone coiling, three were treated with stent-assisted coiling, and two with flow diversion with adjuvant coiling. Microcatheter prolapse occurred in one case of a recurrent aneurysm, due to mechanical limitations imposed by a stent placed during prior coiling. Raymond-Roy Occlusion Classification (RROC) I or II occlusion was achieved in 12 aneurysms, including all 10 undergoing primary stand-alone coiling. Of the five RROC III occlusions, two were expected given treatment with flow diversion, while the other three occurred in complex, recurrent aneurysms. One patient suffered a thromboembolic complication of unclear clinical significance. Conclusions: The Penumbra SMART coil is a safe and effective device for the endovascular treatment of IAs. Follow-up studies are required to establish long-term results.